Synthesis and characterization of thermo-sensitive graft copolymer of carboxymethyl guar and poly(N-isopropylacrylamide) - Gupta, Nivika R.; Ghute, Pallavi P.; Badiger, Manohar V. (Carbohydrate Polymers, 2011)
Thermo-responsive graft copolymers of carboxymethyl guar [CMG] and semitelechelic poly(N-isopropylacrylamide) [PNIPAm] were synthesized by coupling reaction between them using a water-soluble coupling agent namely, 1-(3-(dimethylamino) propyl)-3-ethyl carbodiimide hydrochloride [EDC]. The incorporation of PNIPAm into CMG was confirmed by FT-IR and NMR spectroscopy. The graft copolymers, CMG-g-PNIPAm showed enhanced viscosity as compared to the unmodified CMG in the semi-dilute regime. Due to the presence of a LCST side chains [PNIPAm], the graft copolymers exhibited thermo-responsive nature with respect to temperature which was investigated using pyrene fluorescence probe studies. Although the thermo-responsive property was observed, the thermo-thickening behavior was not seen in these polymers. The graft copolymers in the semi-dilute regime (C(p) approximate to 10-20 g/L) showed viscoelastic properties and the relaxation time, tau, could be obtained from the crossover of frequency (oh) of storage modulus (G') and loss modulus (G `') in the oscillatory experiments. The activation energy `E(a)' of associations was investigated using the time temperature superpsition (TTS). These thermo-responsive polymers along with the biodegradability of CMG can have potential application as industrial thickening agent. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Poly(N-isopropylacrylamide); Thermo-sensitivity and graft copolymer

Synthesis and characterization of PEPO grafted carboxymethyl guar and carboxymethyl tamarind as new thermo-associating polymers - Gupta, Nivika R.; Torris, Arun A. T.; Wadgaonkar, Prakash P.; Rajamohanan, P. R.; Ducouret, Guylaine; Hourdet, Dominique; Creton, Costantino; Badiger, Manohar V. (Carbohydrate Polymers, 2015)
New thermo associating polymers were designed and synthesized by grafting amino terminated poly(ethylene oxide-co-propylene oxide) (PEPO) onto carboxymethyl guar (CMG) and carboxymethyl tamarind (CMT). The grafting was performed by coupling reaction between-NH2 groups of PEPO and -COOH groups of CMG and CMT using water-soluble EDC/NHS as coupling agents. The grafting efficiency and the temperature of thermo-association, T-assoc in the copolymer were studied by NMR spectroscopy. The graft copolymers, CMG-g-PEPO and CMT-g-PEPO exhibited interesting thermo-associating behavior which was evidenced by the detailed rheological and fluorescence measurements. The visco-elastic properties (storage modulus, G'; loss modulus, G'') of the copolymer solutions were investigated using oscillatory shear experiments. The influence of salt and surfactant on the T-assoc was also studied by rheology, where the phenomenon of ``Salting out'' and ``Salting in'' was observed for salt and surfactant, respectively, which can give an easy access to tunable properties of these copolymers. These thermo-associating polymers with biodegradable nature of CMG and CMT can have potential applications as smart injectables in controlled release technology and as thickeners in cosmetics and pharmaceutical formulations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Carboxymethyl tamarind; Pluronics; Rheology; Solution behavior; Thermo-associating polymers